Self selected speed and maximal lactate steady state speed in swimming - Baron, B.; Dekerle, J.; Depretz, S.; Lefevre, T.; Pelayo, P. (The Journal of Sports Medicine and Physical Fitness, 2005)
Aim: The purposes of this study were to ascertain whether physiological and stroking parameters remain stable during a 2-hour exercise performed at self-selected swimming speed (S4) and whether this speed corresponds to those associated with the maximal lactate steady state (SMLSS). Methods: Ten well-trained competitive swimmers performed a maximal 400-m front crawl test, 4 30-min swimming tests in order to determine SMLSS and a 2-hour test swum at their preferred paces to determine self-selected swimming speed (S4), stroke rate (SR4), and stroke length (SL4) defined as the mean values observed between the 5th and the 15th min of this test. The stroking, metabolic and respiratory parameters, and ratings of perceived exertion (CR10) were reported throughout the 2-hour test. Results: S4 and Smlss were not significantly different and were highly correlated (r=0.891). S4 and SL4 decreased significantly after a steady state of 68 min and 100 min, respectively, whereas SR4 remained constant. Mean V.O2, dioxide output, and heart rate values did not evolve significantly between the 10th and 120th minute of the test whereas capillary blood lactate concentration ([La]) decreased significantly (p<0.05). Moreover, respiratory CR10 did not evolve significantly between the 10th and the 120th minute of the test whereas general CR10 and muscular CR10 increased significantly. Conclusion: Considering the [La], SL4 and CR10 values variations, muscular parameters and a probably glycogenic depletion seem to be the main limiting factors that prevent maintaining the self selected swimming speed.